Role of structural ions on the dynamics of the Pseudomonas fluorescens 07A metalloprotease - Alves, Maura P.; Eller, Monique R.; Carvalho, Antonio Fernandes de; Ligabue-Braun, Rodrigo; Polêto, Marcelo D. (Food Chemistry, 2019)
The molecular dynamics of the Pseudomonas fluorescens 07A metalloprotease in the presence of structural Ca2+ and Mn2+ ions was evaluated. Seven Ca2+ ions are primarily bound to the C-terminus, while a divalent cation is located at the catalytic site, acting as a cofactor. The observed enzyme’s experimental activity suggests that Mn2+ could compete for the active site of the enzyme with Ca2+, Zn2+ or other divalent cations, thus providing greater catalytic power to the enzyme. Our molecular dynamics simulations suggest that these ions partially protect the enzyme’s structure from thermal denaturation. Moreover, our simulations have shown a collective movement of opening-closing of the active-site in simulations with structural Ca2+ and Mn2+ ions bound, leading to a proposal of a dynamical model of P. fluorescens 07A metalloprotease active and inactive conformations. These findings can support the development of measures to control the activity of P. fluorescens and other spoilage microorganism proteases.
Keywords: Molecular motion; Enzymatic activity; Molecular dynamics